Enhanced performance in catalytic combustion of toluene over mesoporous Beta zeolite-supported platinum catalyst - Chen, Chunyu; Zhu, Jie; Chen, Fang; Meng, Xiangju; Zheng, Xiaoming; Gao, Xionghou; Xiao, Feng-Shou (Applied catalysis. B, Environmental, 2013)
Mesoporous Beta zeolite-supported Pt catalyst (Pt–R/Beta-H) exhibits much higher catalytic activities and longer catalyst life as well as lower apparent activation energy in combustion of toluene than conventional Beta zeolite-supported Pt catalyst (Pt–R/Beta). This phenomenon could be strongly related to the presence of mesoporosity in Beta-H zeolite, which is favorable for mass transfer and dispersion of Pt particles. •Zeolite-supported Pt catalysts are prepared by incipient wetness impregnation.•Mesoporous Beta catalyst performs excellently in the combustion of toluene.•Mesoporous Beta catalyst has higher activities and longer life than conventional one.•Mesoporosity in zeolite is favorable for mass transfer and Pt particles dispersion.•Reduced mesoporous Pt catalyst performs much lower activation energies (37–46kJ/mol). Removal of volatile organic compounds (VOCs) has recently been attracted much attention, and catalytic combustion is one of good methods for solving this problem. In this research, we show a successful preparation of mesoporous Beta zeolite-supported Pt catalyst (Pt–R/Beta-H) and its superior performance in the catalytic combustion of toluene. N2 sorption isotherms show that the mesopore volume of Pt–R/Beta-H reaches 0.18cm3/g, and TEM images exhibit that the Pt particles exist in both micropores and mesopores of the sample. Interestingly, the Pt particles on Pt–R/Beta-H have higher dispersion than the Pt particles on conventional Beta zeolite (Pt–R/Beta). XPS spectra also reveal that Pt–R/Beta-H has higher Pt0/Pt2+ ratio than Pt–R/Beta. Very importantly, Pt–R/Beta-H exhibits much higher catalytic activities and longer catalyst life as well as lower apparent activation energy in the catalytic combustion of toluene than Pt–R/Beta. The extraordinary performance in the catalytic combustion of toluene over Pt–R/Beta-H catalyst is of great importance for obtaining clean environment and enhancing human health.